Riboflavin (vitamin B2) - Fairweather-Tait, Susan (Henry Stewart Talks, 2026)
Functions in the body, Food sources, Absorption, Metabolism, Effects of genotype, Biomarkers of intake and status, Deficiency, Excess, Dietary reference values for riboflavin for adults